Diseño de un sistema integrado de gestión QHSE para el proceso de lavado de papa en centrales de abastecimiento agropecuario (2015)
The relationship that organizations and production processes have with their environment is linked to three fundamental aspects: Quality, Environment and Safety and Occupational Health. Based on the aforementioned relationship, the so-called Integrated Management Systems are established, which considers certifiable regulations and / or management models, quality NTC ISO 9001: 2008, environment NTC ISO 14001: 2004 and prevention of occupational risks NTC OHSAS 18001: 2007 The problem presented in the potato washing process of the CORABASTOS supply wholesaler plant was addressed, where these three components were diagnosed and subsequently a base management model was formulated that could be replicated in any supply center or production process. national and international level.